2019
DOI: 10.1002/jctb.5933
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Fe3O4‐derived organic/inorganic hybrids constructed by modified bio‐inspired functionalization: efficient adsorbents for water‐soluble methylene blue and mechanism

Abstract: Background The development of efficient and sustainable adsorbents is still a challenge for dye removal in practical applications. Here a method to prepare hierarchical Fe3O4‐derived organic/inorganic hybrid adsorbents for methylene blue removal is demonstrated. Typically, two different structured magnetic nanoparticles were synthesized through solvothermal route and chemical co‐precipitation (named as S‐Fe3O4 and C‐Fe3O4 respectively), which were further functionalized by a novel modified mussel‐inspired meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
12
2
Order By: Relevance
“…(b) appear at 24.5 and 26.5 eV, which are ascribed to the binding energies of Ta (4f 7/2 ) and Ta (4f 5/2 ), respectively. It can be demonstrated that the Ta 2 O 5 has been successfully synthesized . Figure (c) shows the spectrum of Ti.…”
Section: Resultsmentioning
confidence: 86%
“…(b) appear at 24.5 and 26.5 eV, which are ascribed to the binding energies of Ta (4f 7/2 ) and Ta (4f 5/2 ), respectively. It can be demonstrated that the Ta 2 O 5 has been successfully synthesized . Figure (c) shows the spectrum of Ti.…”
Section: Resultsmentioning
confidence: 86%
“…11 The Fe 2p 1 and Fe 2p 3 peaks of the GFA were clearly weaker than the peak of the EGF. Meanwhile, the peaks of N 1s, C-Si (282.4 eV) 52 and C-N, as well as a Fe 2p intensity reduction, were also observed in the total spectrum and the C 1s spectrum of the GFA + KH550 (Fig. S1e and f †).…”
Section: Characterization Of the Compositesmentioning
confidence: 88%
“…S1a †). 11,12,52 The C 1s core-level spectrum of the EGF was divided into four peak components: C-C (284.6 eV), C-O (286.6 eV), C]O (288.4 eV), and O-C]O (290.3 eV) (Fig. S1b †).…”
Section: Characterization Of the Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to rapid industrialization and population growth the release of considerable amounts of dyes from many industries such as textile, leather, paper, plastic, printing, rubber, cosmetic and food processing plants into waters results in serious water pollution. 1,2 Accumulation of dyes in water causes not only contamination, but also adverse impacts on human health. 3,4 Methylene blue (MB) with unfavorable properties is a cationic dye widely used in many industrial applications.…”
Section: Introductionmentioning
confidence: 99%